HUBUNGAN ASUPAN ZAT BESI DAN VITAMIN C, FREKUENSI KONSUMSI MINUMAN BERISIKO, SERTA PERILAKU DIET DENGAN ANEMIA REMAJA PUTRI KOTA DEPOK: Hubungan Asupan Zat Besi dan Vitamin C, Frekuensi Konsumsi Minuman Berisiko, serta Perilaku Diet dengan Anemia Remaja Putri Kota Depok - Fitripancari, Aulia Dewi; Arini, Firlia Ayu; Imrar, Iin Fatmawati; Maryusman, Taufik (Universitas Airlangga, 2023)
Background: Anemia is a condition when the hemoglobin level is lower than normal hemoglobin. In Indonesia, Anemia is a nutritional disorder still commonly found in schools and society environment, especially in female adolescents because they are at an age prone to having hemoglobin deficiency. Objectives: To determine the relationship between iron and vitamin C intake, consumption frequency of risky drinks, and dietary behavior with the incidence of iron deficiency Anemia in female adolescents at SMAN 6 Depok. Methods: This is a quantitative research type that uses a cross-sectional research design. The sample used was 123 respondents of 16 to 18-year-old young females obtained using the stratified random sampling method. Data regarding iron and vitamin C intake and the consumption frequency of risky drinks was obtained through interviews using the Semi Quantitative-Food Frequency Questionnaire (SQ-FFQ) and Food Frequency Questionnaire (FFQ) sheets. While data on female students' dietary behavior was obtained from filling out questionnaires, hemoglobin level data was obtained from direct data collection by competent nursing students. Results: The result of the univariate analysis shows that the incidence of Anemia in female adolescents at SMAN 6 Depok was 13%. Using the chi-square test, the result of bivariate analysis shows that there was a relationship between iron intake (p=0.016), vitamin C intake (p=0.0245), and dietary behavior (p=0.024), and there was no relationship between the frequency of tea consumption (p=1.000) and the frequency of coffee consumption (p=1.000) with the incidence of iron deficiency Anemia in female adolescents at SMAN 6 Depok. Conclusions: Female adolescents need to increase awareness of the incidence of Anemia and preventive behavior by paying attention to iron and vitamin C intake, limiting the consumption of tea and coffee as Fe inhibitors, and implementing healthy dietary behavior.